Pengaruh Manajemen Peternak Terhadap Efesiensi Reproduksi Sapi Bali Di Kabupaten Pringsewu Provinsi Lampung - Sri Suharyati; Madi Hartono (Politeknik Negeri Lampung., 2016)
The aim of this research was to determine the effect of farmer management on Balicattle reproduction efficiency in Pringsewu Regency, Lampung Province. This studywas conducted in August—September 2015 to 108 farmers and 143 Bali with censusmethod. Data were analyzed by logistic regression and multiple regression.The results showed that the CR was 51,75% with kind of grass that negativelyassociated with factor value 0,199, wall of cow’s pen that positively associated withfactor value 1,455, and sanitation of cow’s pen that positively associated with factorvalue 0,510, body conditioning score that negatively associated with factor value0,533 and first mating age that negatively associated with factor value 0,059. The CIwas 416,69 ± 70,03 days with farmer’s reason that negatively associated with factorvalue 28,379, floor of cow’s pen that positively associated with factor value 19,880,age of weaning calf that positively associated with factor value 0,076, first mating agethat positively associated with factor value 0,972, and state of reproduction thatnegatively associated with factor value 125,306. The S/C was 1,76 with farmereducation that negatively associated with factor value 0,200, large of cow’s pen thatnegatively associated with factor value 0,016, and sanitation of cow’s pen thatnegatively associated with factor value 0,297. The RB was 18,18% with farmer’sduration that negatively associated with factor value 0,059, the amount of water thatnegatively associated with factor value 0,058, large of cow’s pen that negativelyassociated with factor value 0,109 and sanitation of cow’s pen that negativelyassociated with factor value 1,154.Key words : Bali cattle, farmer management, CR, CI, SC, RB